Numerical Simulation on Rivulets around Stay Cable Subject to Wind - Bi, Ji Hong; Wang, Jian; Bao, Chun; Lu, Peng (Applied Mechanics and Materials, 2013)
Rain-wind induced vibration (RWIV) is a large amplitude and low frequency vibration of stay cables under wind and rain. The formation and oscillation of rivulets on stay cable surface plays an important role in RWIV, and it is also the symbolic characteristics of RWIV. In this paper, a numerical simulation approach of the formation process of rivulets around stay cable is presented by combining gas-liquid two-phase theory and volume of fluid method (VOF method) for the first time. The effect of gravity and air flow on morphology of rivulets is analysed by numerical simulation using computational fluid dynamics (CFD) software-CFX. The veracity and rationality of this approach is verifed by comparing with existing experimental data.